2021
DOI: 10.1002/lary.29374
|View full text |Cite
|
Sign up to set email alerts
|

Facial Pressure Injuries from Prone Positioning in the COVID‐19 Era

Abstract: Objective/Hypothesis This study aimed to determine the incidence of facial pressure injuries associated with prone positioning for COVID‐19 patients as well as to characterize the location of injuries and treatments provided. Methods This was a retrospective chart review of 263 COVID‐19 positive patients requiring intubation in the intensive care units at MedStar Georgetown University Hospital and MedStar Washington Hospital Center between March 1st and July 26th, 2020. Information regarding proning status, du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
15

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(111 citation statements)
references
References 13 publications
3
63
0
15
Order By: Relevance
“…Proning plays an important role in the development of facial ulcers as indicated by Shearer et al who observed that 47.6% proned COVID-19 patients developed facial pressure ulcers with 84% of them developing ulcers on the cheeks similar to our patient. They also noted a positive association between the risk of facial pressure ulcers and prolonged proning [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Proning plays an important role in the development of facial ulcers as indicated by Shearer et al who observed that 47.6% proned COVID-19 patients developed facial pressure ulcers with 84% of them developing ulcers on the cheeks similar to our patient. They also noted a positive association between the risk of facial pressure ulcers and prolonged proning [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Coyer et al also observed that frequent repositioning of the tubes prevented the injury [ 5 ]. Silicone-based thin foam dressings used as a barrier between the skin and ETT fastener can prevent the development of facial ulcers [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On reviewing the emerging evidence on ICU-related complications in COVID-19 patients, fourteen studies (one cohort study [20], two case-control studies [21,22], one cross-sectional study [23], two case-series [24,25], and eight case-reports [26][27][28][29][30][31][32][33]) with two hundred ten patients met the inclusion criteria. The majority of the cases were from the Americas (USA n = 103, 49.5%; Brazil n = 4, 1.9%), followed by Europe (Spain n = 57, 27.1%; UK n = 16, 7.6%; France n = 2, 1%; and Italy n = 2, 1%), and Middle East (Iran n = 26, 12.4%).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The perioral (facial) pressure ulcers have been the most prevalent ICU-related oral complication in COVID-19 patients reported by ten studies in one hundred seventy-nine patients; 73.75% of them were males, and the vast majority were of old age [20][21][22][23]25,[29][30][31][32][33]. Prolonged pronation and endotracheal intubation were the most evident risk factors for perioral pressure ulcers.…”
Section: Perioral Pressure Ulcers (Icd-11: Eh90)mentioning
confidence: 99%